Imagiological Diagnosis of Gastrointestinal Diseases – Diagnostic Criteria of Hepatocellular Carcinoma - Boal Carvalho, Pedro (GE Port J Gastroenterol, 2015)
Hepatocellular carcinoma (HCC) is one of the leading causes of neoplastic morbidity and mortality worldwide, and despite recent treatment advances, the prognosis remains dismal, with a 5-year mortality rate of 85%. The surveillance and timely diagnosis is therefore of crucial importance in order to improve survival rates and alleviate the health burden imposed by the HCC. Previously, HCC diagnosis warranted liver biopsy, an invasive process with limited diagnostic accuracy. In the past 15 years, HCC diagnosis based solely on imaging criteria was accepted by all the major national and international guidelines, and is now widely employed across the globe. Current European guidelines for the HCC diagnosis support the use of both dynamic contrasted computer tomography as well as magnetic resonance imaging for the non-invasive diagnosis of HCC for nodules >1 cm in a cirrhotic liver. The non-invasive diagnosis of HCC depends on radiological hallmarks, such as homogeneous contrast uptake during the arterial phase and wash-out during the venous and late phases, but while such tumoral behaviour is frequent in nodules >2 cm, high-end equipment and superior expertise is often needed for the correct diagnosis of early HCC. Nevertheless, the accuracy of imaging techniques for the diagnosis of HCC is permanently improving, and supports the progressively reduced need for liver biopsy during liver nodule workout in a cirrhotic liver.